Extended Anterolateral Approach for Complex Lateral Tibial Plateau Fractures - Kfuri, Mauricio; Schatzker, Joseph; Castiglia, Marcello Teixeira; Giordano, Vincenzo; Fogagnolo, Fabricio; Stannard, James P. (The Journal of Knee Surgery, 2017)
Complex fractures of the lateral tibial plateau may extend to the posterior rim of the knee and to the tibial spines. Displaced fractures of the posterolateral corner of the tibial plateau may result in joint incongruity and instability, especially with the knee in flexion. Anatomical reduction of the joint surface and containment of the tibial rim are the primary goals of the treatment in such cases. Dedicated surgical approaches including dissection of the peroneal nerve, sometimes in association with an osteotomy of the fibular head are typically used to address these injuries. Some techniques require special positioning of the patient on the operative table. Anatomical studies of the knee allowed us to conclude that an osteotomy of the lateral epicondyle of the femur may be a natural extension of the standard anterolateral approach to the tibial plateau. The main advantage of this approach is the broad exposure of the lateral joint surface, allowing its anatomical reduction. It does not violate the proximal tibiofibular joint or pose a risk to the peroneal nerve. The main limitation is the lack of visualization of the posterior metaphysis of the tibia, preventing the application of a buttress plate parallel to the plane of fracture split. To overcome this limitation, we describe a method to support the posterior tibial plateau rim, in cases of bicondylar tibial plateau fractures, combining the extended anterolateral with the posteromedial approach. For selected cases, with a significant compromise of the posterolateral and anterolateral quadrants of the tibial plateau, including the tibial spines, the extended anterolateral approach may be complemented by a planned detachment of the anterior horn of the lateral meniscus. In such variant, a complete exposure of the entire surface of the lateral tibial plateau and tibial spines is achievable, assuring optimal conditions for an anatomical reduction of the articular surface.
Keywords: tibial plateau; posterolateral corner; surgical approach; lateral epicondyle osteotomy